Determinants of Customer Satisfaction in Public Transportation Services: Studies on Solo-Yogyakarta Commuter Line - Sarjiyanto, Sarjiyanto; Wahyudi, Lilik; Sarwoto, Sarwoto; Ma'Arif, Miftachul; Manshur Al Ahmad, Ana Shohibul (Jurnal Manajemen Pelayanan Publik, 2024)
The Solo–Yogyakarta commuter line (KRL) has become a popular mode of transport due to its speed, affordability, connectivity, freedom from traffic congestion, and environmental benefits, offering a promising solution to reduce congestion in Solo and Yogyakarta. However, it has not yet attracted the majority of commuters. This research aims to evaluate customer perceptions of service quality on the Solo-Yogyakarta Commuter Line, with a focus on the impact of facilities, memorable experiences, and entertainment on customer satisfaction and loyalty. Using the SEM PLS method, the study found that Entertainment Experience strongly influences Loyalty but not Satisfaction, as KRL users prioritize safety and reliability over leisure. Facilities improve Satisfaction but have a limited impact on Loyalty, indicating that while they are essential, they are not sufficient to build long-term commitment. Memorable Experiences positively affect both Satisfaction and Loyalty, highlighting the importance of creating emotionally engaging moments. Satisfaction alone does not drive Loyalty, emphasizing the need for more meaningful and engaging experiences. Therefore, PT KAI should focus on balancing functional efficiency with emotionally engaging features to better meet customer expectations and foster long-term loyalty.